The pregnancy health and birth outcomes of women who underwent assisted reproductive technology: Results of a national survey - Lii-Shung Huang; Chi-Hwa Yen; Shu-Hsin Lee; Bih-Ching Shu; For-Wey Lung; Ching-Pyng Kuo; Wei-Ya Wu; Angel Yen-Chiao Lu; Yen-Ju Lin; Ming-Chih, Chou; Meng-Chih Lee (Iranian Journal of Reproductive Medicine, 2011)
Background: There is an upward trend for parents to resort to assisted reproductive technology (ART) treatment due to delayed childbirth or birth difficulties.Objective: This study investigates the pregnancy health and birth outcomes of women who underwent ART and analyzes the factors that influence birth weight to become<10 percentile when undergoing ART. Materials and Methods: This study analyzed results of the first wave of the Taiwan Birth Cohort study. Through stratified systematic sampling, 24,200 mother-and-child sampling pairs were obtained from a total of 206,741 live births in Taiwan in 2005; 366 of the babies were born with the use of ART. Results: During pregnancy, mothers who used ART suffered from higher risks of complication than the natural conception counterparts, including gestational diabetes mellitus (GDM), pregnancy induced hypertension (PIH), and placenta previa. Additionally, babies born through ART had poorer outcomes than the natural conception groups: the low birth weight (<2500g) was 33.1% compared to 6.4% for babies born naturally. Conclusion: Pregnancy health and birth outcomes of women who underwent ART were worse than those who got natural conception. Types of maternal complication among ART women included GDM, PIH, and placenta previa. Having multiple births was the most important factor that causes low birth weight in babies. The results of this study can be used as a reference for the health and care of mothers and babies who use ART.